Determining the validity and reproducibility of the Healthy Heart Food Index : a thesis presented in partial fulfilment of the requirements for the degree of Masters of Science in Nutrition and Dietetics at Massey University, Albany, New Zealand - Guy, Harriet (Massey University, 2019)
Background: Diet quality is associated with cardiovascular disease (CVD) risk, and the New Zealand (NZ) Heart Foundation has produced dietary guidelines aimed at reducing CVD risk for adult New Zealanders. At present, there is no valid and reproducible diet quality index for older adults living in NZ, which focuses on CVD risk. Aim: To develop and determine the construct validity and reproducibility of the Healthy Heart Food index (HHFI) for measuring dietary patterns in older adults living in New Zealand. Method: The HHFI was developed based upon NZ Heart Foundation Guidelines. To assess HHFI reproducibility, 298 community dwelling participants aged 65-74 years completed the HHFl twice approximately four-weeks apart. To validate the index, 142 of these participants completed a four-day food record (4DFR). Construct validity was explored using Spearman's correlation coefficients and linear contrast analysis of selected nutrients from the 4DFR. Spearman's correlation coefficients, Wilcoxon ranked-signed tests, cross-classification, the weighted kappa statistic, and a Bland-Altman plot were used to assess HHFl reproducibility. Results: Mean HHFl total scores were 693i10.8 and 68.9i11.1 from the first and second HHFl administrations respectively. These scores were positively correlated (r= 0.662, P<0.001) and cross-classification showed 55.4% of participants were categorised into the same fertile and 6.3% were grossly misclassified. The weighted kappa statistic was K: 0.43, indicating moderate agreement between HHFI total scores. For construct validity, iron (r= 0.201), vitamin C (r= 0.174), and niacin (r= 0.205) (all P<0.05), and protein (r= 0.277), polyunsaturated fatty acids (r= 0.236), dietary fibre (r= 0.307), vitamin (r= 0.205), folate (r= (1268), potassium (r= 0.246), magnesium (r= 0.300), phosphorus (r= 0.281), zinc (r= 0.276), and selenium (r= 0.222) (all P<0.01), were positively correlated with the HHFI total score. Saturated fat and cholesterol were negatively correlated (r= -0.097 and -0.035 respectively) with the HHFI total score, however this was a non-significant association (P>0.05). Linear contrast analysis showed a significant positive association between polyunsaturated fat, monounsaturated fat, dietary fibre, potassium, folate (P<0.05), vitamin E (P<0.01), and magnesium (P<0.005) and HHFI total scores. Conclusion: Moderate adherence to the HHFI was shown in this population sample. Results indicate the HHFI demonstrated construct validity and good reproducibility for assessing CvD-related diet quality in older adults living in New Zealand. Further research is needed to examine the predictive validity of this index in relation to CVD risk.
Keywords: Cardiovascular system; Diseases; Nutritional aspects; New Zealand; Risk factors; Older people; Nutrition; Evaluation; diet quality index; validity; reproducibility; cardiovascular disease; 321004 Nutritional science